Analysis of the Business Feasibility Study of Zinnia's Activewear Modest Series Product Innovation as a Functional and Sustainable Muslim Fashion - Nida Ul Hasanah; Eka Purwanda (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study provides an in-depth analysis of the business feasibility of Zinnia Activewear Modest. An innovative sportswear product designed especially for Muslim women who are looking for functional and simple sportswear. This study uses a qualitative descriptive approach with a multidimensional feasibility analysis to explore various aspects such as management, marketing, production, human resources, finance, environment, and legality, as well as SWOT analysis. Financial analysis shows that Zinnia is a very good investment, because the return on capital period is 1.5 years, Net Present Value (NPV) with an interest rate of 12% is IDR 266,936,920, Profitability Index (PI) of 3.78, Internal Rate of Return (IRR) of 79.43%, Average Rate Return (ARR) of 109.49%, and Break Even Point 3,960 units per year. The SWOT analysis shows that there is a large market opportunity because Indonesia has Zinnia Activewear Modest products that are financially feasible and strategically ready to enter market segments that have not been previously met in the Muslim sportswear industry.